Valorization of the essential oil from Drypetes gossweileri S. Moore (Putranjivaceae): in vitro, in vivo, and in silico nematicidal activity - Mbula, Jean Pierre; Andres, Maria Fe; Kitete, Emmanuel M.; Kasiama, N. G.; Tshilanda, D. D.; Ngbolua, K. N.; Tshibangu, D. S. T.; Onautshu, O.; González-Coloma, Azucena; Mpiana, Pius T. (Frontiers in Plant Science, 2023)
The chemical composition, the insect antifeedant, in vtro/ in vivo nematicidal activity, phytotoxicity and and in silico nematicidal activity of the essential oil (EO) of the African medicinal plant Drypetes gossweileri was studied. The chemical analysis by GC/MS indicated that benzyl isothiocyanate (96.23%) was the major compound, followed by benzyl cyanide (1.38 %). The biocidal effects of the oil were tested against insect pests and root-knot nematodes. All the insect species tested were significantly affected by the oil according to their feeding adaptations (Spodoptera littoralis and Myzus persicae were less affected than Rhopalosiphum padi) with efficient doses (EC50) of 29.4, 14.744 and 8.3 g/cm 2 respectively.The oil was very effective against juveniles J2 of the nematode Meloidogyne javanica, with LC50-LC90 values of 0.007-0.0113 mg/mL, respectively. D. gossweileri EO at minimum lethal concentrations (MLC) and below strongly inhibited egg hatching in vitro, while soil treatment caused a strong suppression of nematode population, infection frequency and multiplication rate. The EO inhibited ryegrass (Lolium perenne) germination at 0.4 mg/mL, while at 0.1 mg/mL, the effects on germination, root and leaf growth were moderate (32.4, 8.4 and 18.3%). The tomato (Solanum lycopersicum) germination was not affected by the EO, but the root growth was reduced (56% at 0.1 mg/mL) at a dose 10 times higher than the LD50 calculated for M. javanica J2 mortality. Molecular docking on the nematicidal effects of the oil using PyRx revealed a strong interaction between potassium-chloride co-transporting KCC3 (PDB ID: 7D90) and the molecule of benzyl cyanide at a distance of 2.20A°with GLN C:350 followed by benzyl isothiocyanate at a distance of 2.78A°with the ARG B:294. The in vivo nematicidal effects of D. gossweileri EO on M. javanica penetration and reproduction in tomato roots further support the potential of this EO as a nematicidal agent with insect antifeedant effects that could be used by local farmers for crop protection.